Selective Depression of the Xenogeneic Cell-Mediated Lympholysis in Systemic Lupus Erythematosus - Charpentier, B. (1979)
The immunological responsiveness of a panel of 17 patients with systemic lupus erythematosus (SLE) was studied in an in vitro model of xenogeneic sensitization against mouse lymphoid cells. Generation of cytotoxic thymus-derived (T) cells evaluated by a chromium release assay against labeled target cells was found to be drastically impaired in these lupus patients. Such depression was independent of drug therapy at the time of the study, clinical status, and other immunological parameters such as antibodies against native DNA, complement levels, cryoglobulinemia, circulating immune complexes, or T- and bone marrow-derived (B)-cell numbers. In contrast to the cytotoxic response, the proliferative responses to phytohemagglutinin, to allogeneic lymphocytes, and to xenogeneic lymphocytes were not significantly different from those of normal individuals. The latter response was shown to be H-2 restricted with the primed lymphocyte test. These results suggest the presence of a selective defect in the generation or in the expression of killer cells rather than a deficiency in antigen recognition by T cells. The role of serum factor(s) was examined by educating the lymphocytes of normal subjects in the presence of serum from SLE patients. Such manipulation affected both the generation of killer cells and the proliferative response. Finally our observations indicate that depression of cell-mediated immunity in SLE patients may be associated with several mechanisms including a cellular one, specifically affecting the generation of killer T cells, and a humoral one possibly as a result of antilymphocytic antibodies and(or) immune complexes.